Cardiovascular risks associated with adjuvant endocrine therapy in women with breast cancer: a population-based cohort study - Iokfai Cheang; Ying Gue; Mei-Zhen Wu; Jia-Yi Huang; Qing-Wen Ren; Ziqi Chen; Yi-Kei Tse; Hang-Long Li; Yap-Hang Chan; Hung-Fat Tse; Xinli Li; Gregory Y. H. Lip; et al. (BMC Cancer)
Abstract Background Endocrine therapies, including tamoxifen (TMX) and aromatase inhibitors (AIs), are widely used in breast cancer treatment. This study aims to evaluate the cardiovascular risks associated with these therapies in different age groups of non-metastatic breast cancer patients. Methods We conducted a cohort study using data from patients newly diagnosed with non-metastatic breast cancer. Patients were categorized into two ages (< 45 years and > 55 years) and then divided into groups based on whether they were newly receiving either TMX or AI. Follow-up continued until the first occurrence of a study outcome, death, or the last date of data collection (December 31, 2022). Primary outcomes were coronary artery disease, myocardial infarction (MI), ischemic stroke, hospitalization for heart failure (HHF), atrial fibrillation (AF), cardiovascular mortality, all-cause mortality, and major adverse cardiovascular events (MACE). Results Among patients < 45 years old, 2837 were newly treated with TMX (n = 2370) or AI (n = 467). During a median follow-up of 8.4 years, the incidence rates of coronary artery disease (5.6 vs. 6.6 per 1000 person-years), myocardial infarction (1.0 vs. 1.7 per 1000 person-years), ischemic stroke (1.5 vs. 1.5 per 1000 person-years), and cardiovascular mortality (1.4 vs. 1.5 per 1000 person-years) were similar between TMX and AI users, with no significant differences in hazard ratios or cumulative incidence curves. However, AI users had a higher risk of HHF (Weighted HR, 3.08 [95% CI, 1.54–6.13], P = 0.001) and AF (P = 0.039) compared to TMX users. For MACE, there was a non-significant elevated risk (Weighted HR, 1.59 [95% CI, 0.90–2.81]), suggesting a trend toward increased risk. Among patients > 55 years old, 11,846 were newly treated with TMX (n = 6577) or AI (n = 5269). During a median follow-up of 5.0 years, AI users had a significantly increased risk of primary cardiovascular outcomes, including CAD, MI, ischemic stroke, HHF, AF, cardiovascular mortality, and MACE (all P < 0.01). Conclusion The study indicates that AIs are linked to a higher risk of cardiovascular events in post-menopausal patients compared to TMX. In younger patients, TMX’s protective effect on cardiovascular outcomes may be less pronounced. Further large-scale studies are required to corroborate and address limitations related to menopausal status and residual confounding.